Study on Seroprevalence and Associated Risk Factors of Newcastle Disease in Smallholder Poultry Farms in Sodo Zuria District, Wolaita Zone, Southern Ethiopia - Saliman Aliye; Habtamu Endale; Mesfin Mathewos; Haben Fesseha (Advances in Virology)
Newcastle disease (NCD) is a highly contagious viral disease of poultry and remains a constant threat in poultry farms that causes huge economic losses. The objective of this study was to estimate and assess the seroprevalence and associated risk factors of Newcastle disease in the Sodo Zuria district, southern Ethiopia. A cross-sectional survey followed by a simple random sampling technique was conducted from May to July 2021 on 384 apparently healthy nonvaccinated chickens on 30 smallholder poultry farms using commercial indirect ELISA kits and a questionnaire survey. The data were analyzed by using STATA for windows version 20 and a logistic regression reporting odds ratiowas applied to describe the seroprevalence of Newcastle disease with associated risk factors. The result of the study demonstrates that there was a high seroprevalence 48.7% (n= 187/384) of Newcastle disease in the study district. Information on associated risk factors were assessed using a semistructured questionnaire. The sex of the chicken showed a statistically significant difference (x2 = 4.842; p = 0.028) with the seroprevalence of the disease. The difference in seroprevalence among intensive, semi-intensive, and extensive management system was statistically significant (x2 = 3.84; p = 0.0001). There was also a statistical significant difference (x2 = 2.3854; p = 0.496) in the absence and presence of safe disposal of a dead chicken with the occurence of Newcastle disease. However, no statistically significant difference was observed among age groups (x2 = 4.335; p = 0.114), disinfection of poultry house (x2 = 0.0; p = 0.998), presence and absence of footbath (x2 = 2.969; p = 0.085), the breeds (x2 = 4.490; p = 0.106), type of chicken (x2 = 0.302; p = 0.583), and housing system (x2 = 1.926; p = 0.588). A high seroprevalence without vaccination history showed that the virus was circulating within the poultry. Therefore, further molecular study has to be conducted to identify circulating strains and develop an evidence-based control program.